Pengaruh Stres Kerja Terhadap Kinerja Guru SMA Negeri 1 Ambon Di Kota Ambon - Yohanes Pattiasina; Stenly R. Titioka; Join R. Luturmas (P3M Politeknik Negeri Ambon, 2023)
Based on an initial survey of teachers at SMA Negeri 1 Ambon, it shows that there are indications of work stress symptoms which have an impact on teacher performance. This research aims to test and analyze the influence of work stress on the performance of teachers at SMA Negeri 1 Ambon. The analysis method used in this research is descriptive analysis and simple linear regression analysis. The results of the hypothesis test show that the Job Stress variable has a positive and significant influence on the performance of SMA 1 Ambon teachers. This can be proven by the results of a simple regression analysis test of variable Job Stress with Teacher Performance, and the R square value is 0.608 or around 60.8%. This means that the influence of the independent variable (Work Stress) on the dependent variable (Performance) is 60.8% while the remaining 39.2% is influenced by other variables which were not examined in this research. Based on the results of this research, it can be concluded that the higher the work stress, the lower the teacher's performance. To overcome this, we must try to reduce teachers' work stress levels by paying attention to the symptoms of work stress on psychological, physical and behavioral indicators so that teacher performance increases. Keywords: Job Stress, Performance